The Management of Patients With Idiopathic Pulmonary Fibrosis - Spagnolo, Paolo; Tzouvelekis, Argyris; Bonella, Francesco (Frontiers in Medicine, 2018)
Idiopathic pulmonary fibrosis (IPF), the most common form of fibrosing idiopathic interstitial pneumonia, is an inexorably progressive disease with a 5-year survival of approximately 20%. In the last decade, our understanding of disease pathobiology has increased significantly and this has inevitably impacted on the approach to treatment. Indeed, the paradigm shift from a chronic inflammatory disorder to a primarily fibrotic one coupled with a more precise disease definition and redefined diagnostic criteria have resulted in a massive increase in the number of clinical trials evaluating novel candidate drugs. Most of these trials, however, have been negative, probably because of the multitude and redundancy of cell types, growth factors and profibrotic pathways involved in disease pathogenesis. As a consequence, until recently IPF has lacked effective therapies. Finally, in 2014, two large phase 3 clinical trials have provided robust evidence that pirfenidone, a compound with anti-fibrotic, anti-oxidant and anti-inflammatory properties, and nintedanib, a tyrosine kinase inhibitor with selectivity for vascular endothelial growth factor, platelet-derived growth factor and fibroblast growth factor receptors are able to slow down functional decline and disease progression with an acceptable safety profile. While this is a major achievement, neither pirfenidone nor nintedanib cures IPF and most patients continue to experience disease progression and/or exacerbation despite treatment. Therefore, in recent years increasingly more attention has been paid to preservation of quality of life and, in the advanced phase of the disease, palliation of symptoms. Lung transplantation, the only curative treatment, remains a viable option for only a minority of highly selected patients. The unmet medical need in IPF remains high, and more efficacious and better tolerated drugs are urgently needed. However, a truly effective therapeutic approach should also address quality of life and highly prevalent concomitant conditions and complications of IPF.